Análise econômica do sistema de produção ILP-integração lavoura pecuária em uma unidade de pesquisa avançada da EMBRAPA do Mato Grosso - Prado, Wander Bosco Souza do (Universidade Federal de São Carlos, 2011)
The purpose of the study was to evaluate the economic viability of Crop-Livestock Integration System (SILP) in a experimental unit of EMBRAPA, stade of Mato Grosso, Brazil. The research was held on 100 hectare farm area under commercial conditions of production. This production system can be considered as an alternative for tradictional land use. It is able to increase agricultural production and avoide exploitation of new agricultural areas in environmental sensitive areas. A case study exploratory research was conducted. The approach to the problem was quantitative and qualitative, by the use of statistical tools for data collection and processing, and the analysis of variables. It was collected economic and financial data in real conditions using spreadsheet software. This information was presented by means of cash flow, which allowed to produce economic indicators and analysis, since the implementation of the project until the marketing of the products for a period of 5 (five) years farming, providing relevant analysis and interpretation of indicators based on analysis of cash flow, such as NPV. An economic analisys of the SILP is provided, showing its advantages and disadvantages for farmers and giving more information for analysis and decision making related to its adoption. It was shown that SILP is economically advantageous when compared with the monoculture of soybean. Even though SILP is a technology still under development, it proved to be advantageous because positive economic returns, and especially because it provides diversification of productive activities, generating greater stability at less risk.
Keywords: Engenharia de produção; Análise de viabilidade; Bovino; Integração lavoura pecuária; Análise de viabilidade econômica; Pecuária bovina; Crop-livestock integration system; Economic evaluation; Beef cattle; ENGENHARIAS::ENGENHARIA DE PRODUCAO